Rethinking the 8th AJCC System: Is It Suitable for Patients Aged <55 Years With Stage T4N1M0 Follicular Variant of Papillary Thyroid Carcinoma to Be Placed in Stage I? - Long, Wei; Hu, Di; Zhou, Ling; Huang, Yueye; Zeng, Wen; Chen, Sichao; Huang, Yihui; Li, Man; Wang, Min; Zhou, Wei; Huang, Jianglong; Wei, Wei; et al. (Frontiers in Oncology, 2020)
Purpose: The newest (8th) edition of the TNM staging system published in 2017. In this edition, some significant changes happened from the previous edition. As a result, down-staging appeared in nearly one third of DTC patients. However, we don’t know whether the new system predicts the survival of FVPTC patients accurately. Therefore, it is necessary to thoroughly evaluate the correlation between the new system and survival prediction in terms of FVPTC. Methods: We enrolled 17,662 FVPTC patients from the Surveillance, Epidemiology, and End Results database. Factors associated with survival were identified by Cox regression analyses. The mortality rates per 1,000 person-years were calculated and compared. Cox proportional hazards regression quantified the risk of survival, and survival curves were produced by Kaplan-Meier analyses using log-rank tests. Results: Age at diagnosis, race, T-stage at diagnosis, distant metastasis, radiation therapy, and surgery were independent factors associated with cancer-specific survival. Patients aged <55 years with stage T4N1M0 FVPTC had higher mortality rates per 1,000 person-years than patients in the same stage according to the 8th AJCC System. Cox proportional hazards regression reflected that patients aged <55 years with stage T1-3, any N, M0 or T4N0M0 disease (p=0.001) and patients aged ≥55 years with T1-2N0M0 disease (p=0.004) had signiﬁcantly lower risks of cancer-specific survival (CSS) than those aged <55 years with stage T4N1M0 disease. The CSS curve of patients aged <55 years with stage T4N1M0 disease showed a decline on comparison with others belonging to stage I (p<0.001); and the curve was even not different from patients in stage II and stage III (p>0.05). Conclusion: Patients aged <55 years with stage T4N1M0 FVPTC had worse survival than patients in stage I; no difference was seen on comparison with stage II patients. We recommend this group of patients be upstaged in the 8th AJCC system.